Implementation of the Gravity Location Models Method in Determining Regional Warehouse Locations to Minimize Goods Transport Costs at PT - Zukrufiawan, Muhammad Adam; Febryanto, Indra Dwi (UNIPA PRESS, 2024)
Supply Chain is a network of companies that work together to create and deliver a product to the end user. PT X is a company engaged in manufacturing whose products are steel pipes, not only steel pipes are produced. Supply chain management at PT X is considered inefficient because it has to supply four warehouses or depots at once, this can cost a lot of shipping costs in the PT X Supply Chain process. Therefore, supply chain management needs to be carried out using the Gravity Location Model method which aims to minimize the costs of transporting goods at PT X. The aim of this research is to determine the variables needed to determine the location point of PT X regional warehouse using the Gravity Location Model method and to determine the regional warehouse location and optimal shipping costs using the Gravity Location Model method at PT X. From the results of research that has been carried out, the variables used to determine the location points for PT X regional warehouse construction include X and Y, Xn and Yn, dn, Cn, Dn, and TC as well as calculating cost minimization through a comparison of 20 iterations, it was found that the minimum cost was in the 11th iteration, namely IDR 386.955,50. with coordinates X = -4.13 and Y = 115,18.